TINDAK PIDANA KEKERASAN FISIK DALAM KEKERASAN RUMAH TANGGA - Siregar, Putri Dharmayanti; Harisman, Harisman (Legal Standing : Jurnal Ilmu Hukum, 2024)
The majority of victims of domestic violence are adolescent girls and women. The objectives of this study were to: 1) characterize various forms of physical violence included in domestic violence crimes and the legal protection provided to victims; 2) characterize the legal provisions for those who commit acts of physical violence; and 3) ensure appropriate action to impose penalties for those who commit acts of physical violence in domestic violence. The Medan District Attorney's Office has been consulted and to obtain information on books, journals, official newspapers, and other sources related to the law and the subject of this study, interviews were conducted to obtain data and legal documents. legal sanctions that will be applied by the Medan District Attorney's Office against various types of domestic violence in 2023, as well as legal protection that will be received by victims of domestic violence. This study can be categorized as field research because it examines relevant legal provisions and social realities using an empirical framework. Perpetrators of domestic violence are subject to several laws and regulations, such as Article 44 paragraph 23 of 2004, the Criminal Code, and the Child Protection Law. The heaviest punishment should be imposed on those who commit acts of physical violence in the household to deter such behavior and make others aware of the consequences that will occur. In order for the state and society to meet the needs of victims for a sense of security and kindness, victims of domestic violence must receive legal protection.